Local Code: Real Estates - Nicholas de Monchaux (Oz, 2015)
Popular images of entropy—a breaking glass, the lowering heap of compost, even our own descent into dust, provide a familiar, but subtly inaccurate thermodynamic picture. Viewed through an informational as well as physical lens, entropy is not a consistent movement towards flatness and uniformity, but something else as well.